1992
DOI: 10.1098/rsta.1992.0048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of global-scale, steady-state convection and elastic-gravitational asphericities on helioseismic oscillations

Abstract: In this paper we derive a theory, based on quasi-degenerate perturbation theory, that governs the effect of global-scale, steady-state convection and associated static asphericities in the elastic-gravitational variables (adiabatic bulk modulus κ, density ρ, and gravitational potential ∅) on helioseismic eigenfrequencies and eigenfunctions and present a formalism with which this theory can be applied computationally. The theory rests on three formal assumptions: (1) that convection is temporally steady in a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 70 publications
0
85
0
Order By: Relevance
“…3 for Runs B0-B3. The convective velocities u can be decomposed in terms of poloidal (u P ) and toroidal (u T ) parts following Lavely & Ritzwoller (1992) …”
Section: Resultsmentioning
confidence: 99%
“…3 for Runs B0-B3. The convective velocities u can be decomposed in terms of poloidal (u P ) and toroidal (u T ) parts following Lavely & Ritzwoller (1992) …”
Section: Resultsmentioning
confidence: 99%
“…We do not include the di †erential rotation, which is described by axisymmetric toroidal velocity Ðelds and is only weakly time dependent. Moreover, di †erential rotation only causes coupling within a multiplet, and no coupling between di †erent multiplets (Lavely & Ritzwoller 1992). Also, we do not investigate the e †ect of the spatial variation of the sound speed in this paper.…”
Section: T Ime-dependent Couplingmentioning
confidence: 99%
“…For toroidal velocity Ðelds, which are related to the di †erential rotation, the coupling occurs only within a multiplet and leads to the well-known antisymmetric rotational splitting of degenerate mode frequencies. Roth & Stix (1999), following the work of Lavely & Ritzwoller (1992), found that poloidal Ðelds lead to a small additional asymmetric shift of the frequencies because of the coupling of modes from di †erent multiplets.…”
Section: T Ime-dependent Couplingmentioning
confidence: 99%
See 2 more Smart Citations